The relationship between private economic growth and public nonmilitary infrastructure capital stock: an empirical study of the U.S. economy - Celebi, Mehmet Ali (Kansas State University, 2007)
This dissertation has focused primarily on the relationship between aggregate private output and a measure of the public fixed capital stock for the U.S. economy using two different approaches for the years 1947-2005. The study starts with a brief survey of the existing literature on the relationship between private output and public capital and continues with an analysis of data on some macroeconomic variables related to private output and public capital. It employs a production function approach to provide empirical estimates and analyze its econometric problems, and continues with a vector autoregression (VAR) model. It uses two criteria, the Akaike Information Criterion and the Schwartz Bayesian Criterion, to compare the performance of the two models tested. There are several differences between this study and the existing literature. The most important difference is that each of the other studies uses only a single approach to analyze the relationship between the public capital stock and private economic growth while this study uses two different methodologies to analyze the same relationship and tests the two models using the same aggregate macroeconomic annual data on the U.S. economy from 1947 to 2005. This study represents the first attempt to provide estimates of the elasticities of private output with respect to the private capital stock, private labor stock, public nonmilitary capital stock, and public core infrastructure capital stock by employing two different approaches so that the comparison of the elasticities resulting from the two different approaches can be most meaningful. Moreover, this study also represents the first attempt to provide estimates of the marginal products of the above four inputs. Second, the studies that employ a production function approach are ad hoc and so is the production function approach of this study, but the production function approach section of this study is the only one having an explicit capital evolution equation for both the private and the public capital stock. All of the other studies using annual data use aggregate macroeconomic data on related variables for less than thirty years while this study employs aggregate data from 1947 to 2005 (fifty nine years). Lastly, the other production function studies are incomplete in the sense that they either do not attempt to deal with some major econometric problems such as a common trend (resulting in a spurious correlation) and the direction of the causation or when they do acknowledge major econometric problems, they do not do anything to correct them. This study, on the other hand, will try to detect major econometric problems. Once the problem is detected, the study will employ measures to deal with the problem. Major findings of this study are as follows. First, the causation runs from the public fixed capital stock to private output rather than in the other direction. Second, most of the studies in the existing literature report a positive impact of the private fixed capital stock on private output that is too small to be credible, whereas they report a positive impact of the public fixed capital stock on private output that is too large to be credible. However, the estimates of this study suggest not only a positive impact of the public capital stock on private output that seems credible but also a positive and very large impact of the private capital stock on private output. Third, the results of several joint hypothesis tests conducted show that there is enough sample evidence to claim that not only that the private sector operates under constant returns to scale in all inputs, private and public, for the years 1947-2005 but also that the private fixed capital stock is more important to the aggregate private production process than either of the two measures of the public fixed capital stock.
Keywords: economic growth; vector autoregression; public fixed capital; Economics, Finance (0508); Economics, General (0501); Economics, Theory (0511)